EGR1 regulates oxidative stress and aldosterone production in adrenal cells and aldosterone-producing adenomas - Yingxian Pang; Siyuan Gong; Martina Tetti; Zhuolun Sun; Sanas Mir-Bashiri; Martin Bidlingmaier; Thomas Knösel; Eckhard Wolf; Martin Reincke; Elisabeth Kemter; Tracy Ann Williams (Redox Biology)
Aldosterone-producing adenomas (APAs) are a major cause of primary aldosteronism, a common form of endocrine hypertension. Here, we demonstrate that Early Growth Response 1 (EGR1) plays a dual role in adrenal cell biology, regulating both oxidative stress and aldosterone production. Using RNA sequencing of RSL3-treated human adrenal cells and spatial transcriptomics of adrenal glands from patients with primary aldosteronism, we identify EGR1 as a key gene associated with RSL3-related oxidative stress and APAs. We show that EGR1 silencing decreases oxidative stress and increases CYP11B2 gene expression and aldosterone production in adrenal cells, while its overexpression has the opposite effects. Notably, EGR1 expression is downregulated in APAs and aldosterone-producing micronodules compared to the adjacent adrenal cortex, which correlates in part with decreased levels of oxidative stress markers. The adrenal cortex of pigs with secondary hyperaldosteronism shows decreased immunostaining of EGR1 and a marker of oxidative stress, suggesting a potential link between EGR1 expression, oxidative stress levels, and adrenocortical function. These findings reveal a novel mechanism linking EGR1 to oxidative stress regulation and aldosterone production in adrenal cells, with potential implications for the pathogenesis of APAs and other adrenocortical tumors.